Experimental and computational investigation of a load-posted steel beam bridge. (15th October 2021) - Stieglitz, Matthew; Terzioglu, Tevfik; Hueste, Mary Beth D.; Hurlebaus, Stefan; Mander, John B.; Paal, Stephanie G.
Highlights: Steel girders bridges with cast-in-place concrete decks may exhibit a certain degree of composite action, even when there are no shear connectors. Consideration of this composite deck and girder behavior can improve load ratings. The AASHTO LLDFs can be quite conservative for some bridge geometries, and more accurate LLDFs can lead to improved bridge load ratings. Refined analysis can provide a more accurate prediction of the live load effects on individual girders of a bridge. Load testing results can also be used to determine load distribution and to verify FEM models. These approaches can produce improved load ratings for some steel girder bridges and possibly the removal of load postings. Abstract: Bridges that are posted for load can cause a variety of issues for the people that use them and the entities that manage them. Load postings generally create detours for routes between origins and destinations of freight trucks, thereby causing additional traffic and a major impact on economic vitality. Load-posted bridges also create management issues for the state departments of transportation as they may require more stringent monitoring, inspection, and maintenance. For these reasons, it is desirable for states to have as few load-posted bridges in their inventory as possible. This paper examines an individual steel beam bridge and presents a methodology that led to the improvement of the load rating of the bridge in a safe and appropriate manner through load testing and refined modeling. The results of the load tests were used to develop new rating factors for the test vehicle and finite element method analysis models were used to develop new rating factors for the HS-20 design truck. It was found that the bridge exhibited rating factors much higher than what it was posted for, and therefore the posting could be removed.